The Kantian Categorical Imperative and Marawi Refugees: Affirming the Importance of the Anti-Terrorism Law - Sheldon Ives G. Agaton (Faculty of Social and Political Science, Universitas Airlangga, 2022)
Immanuel Kant’s Categorical Imperative teaches a single moral obligation for every human person. Regarded by many as the most influential philosopher during the modern era, his ethical emphasis was on the deontological moral system as the basis of man’s actions rather than ethics based on subjective considerations. This paper uses an interpretive analysis of the Kantian doctrine intertwined with the treatment of refugees in the war-torn Marawi in 2017. Refugees and other victims of this human strife fled Marawi City and settled in other towns with the help of the government and other people and organizations. Terrorism did not stop in that year as this activity can still be felt all over the world. Even today, the Philippine government still deals with terroristic acts despite the promulgation of the Anti-Terrorism Act of 2020 and hopes to finally minimize if not end the brutal attacks brought about by terrorism. The actions of certain people helping refugees conform with this Kantian doctrine, specifically on Duty, Good Will, and Hospitality. The necessity of an Anti-Terrorism Law is also explained to put an end to or minimize terror attacks in the country despite objections from certain groups.